Encapsulation of two-dimensional materials inside carbon nanotubes: Towards an enhanced synthesis of single-layered metal halides. (October 2017) - Sandoval, Stefania; Pach, Elzbieta; Ballesteros, Belén; Tobias, Gerard
Abstract: The unique properties of two-dimensional (2D) nanomaterials make them highly attractive for a wide range of applications. As a consequence, several top-down and bottom up approaches are being explored to isolate or synthesize single-layers of 2D materials in a reliable manner. Here we report on the synthesis of individual layers of several 2D van der Waals solids, namely CeI3, CeCl3, TbCl3 and ZnI2 by template-assisted growth using carbon nanotubes as directing agents, thus proving the versatility of this approach. Once confined, the metal halides can adopt different structures including single-layered metal halide nanotubes, which formation is greatly enhanced by increasing the temperature of synthesis. This opens up a new strategy for the isolation of individual layers of a wide variety of metal halides, a family of 2D materials that has been barely explored. Graphical abstract: